The Group Supportive Therapy Model and Disaster Preparedness Training in Improving the Preparedness of School Community Toward Disaster in West Sumatera - Renidayati; Zolla Amely Ilda; Reflita (proceedinginternational, 2023)
West Sumatra gets the fifthranks in the top disaster-prone province in Indonesia. The level of disaster preparedness in the school environment is at the lowest position compared to the preparedness in the community. This study aimed to implement the Model Group Supportive Therapy and Disaster PreparednessTraining to improve the school community's preparedness for disasters in West Sumatra. The research design used "Quasi experimental pre-post test without control group". It was carried out in four public elementary schools in Pariaman and Padang with 166 respondents taken by purposive sampling. The results of the first stage of the study showed an increase in preparedness to face potential disasters in students before and after being given the Model Group Supportive Therapy Model and Disaster Preparedness Training. There was an increase in preparedness to face potential disasters by 23,614 students. The Group Supportive Therapy model and disaster preparedness training program are effective in increasing school preparedness against potential disasters by 62.71%. It is recommended to the Education Office in West Sumatra that elementary school communities receive Model Group Supportive Therapy training and Disaster Preparedness School Training. The completion of the Model Group Supportive Therapy module and disaster preparedness training program needs to be carried out as one of the interventions in an effort to increase school community preparedness against potential earthquake disasters and the tsunami in West Sumatra.